Hexagonal ring origami—Snap-folding with large packing ratio. (May 2022) - Wu, Shuai; Dai, Jize; Leanza, Sophie; Zhao, Ruike Renee
Abstract: Hexagonal and hexagon-based structures are widely seen in nature and inspire various engineering designs by demonstrating capabilities of tessellating complex two-dimensional (2D) and three-dimensional (3D) assemblies. While enabling functionality at the deployed state, folding hexagonal structures to a greatly reduced area or volume allows for space-saving for transportation. However, the study on an effective folding strategy is limited. In this work, we report a snap-folding strategy for hexagonal rings, which results in a folded state with only 11% of the initial area. Through finite element analysis and experimental validation, the influence of geometric parameters, loading methods, and loading locations on the hexagonal rings' foldability and stability is investigated systematically. Triggered by buckling instability under bending or twisting, hexagonal rings demonstrate precise and self-guided folding with high flexibility and a high tolerance to loading fluctuations. It is anticipated that the hexagonal ring origami could provide a new strategy for designing functional large foldable structures with self-guided deformation and an excellent packing ratio.